2005
DOI: 10.3168/jds.s0022-0302(05)72895-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic Parameters for Canadian Holstein Female Reproduction Traits

Abstract: Age at first insemination, days from calving to first insemination, number of services, first-service nonreturn rate to 56 d, days from first service to conception, calving ease, stillbirth, gestation length, and calf size of Canadian Holstein cows were jointly analyzed in a linear multiple-trait model. Traits covered a wide spectrum of aspects related to reproductive performance of dairy cows. Other frequently used fertility characteristics, like days open or calving intervals, could easily be derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
221
15
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(303 citation statements)
references
References 38 publications
(55 reference statements)
60
221
15
7
Order By: Relevance
“…In addition, they reported that the heritability of DO was 0.05 for both parities and estimates of heritability for FSCR was 0.01 in first lactation and 0.0 in second lactation. Consistent with our results, Jamrozik et al (2005) reported heritabilities of most reproductive traits were generally below 0.10. Table 3 shows genetic and phenotypic correlations among reproductive performance traits and Table 4 shows genetic and phenotypic correlations among MUN and reproductive performance traits.…”
Section: Resultssupporting
confidence: 91%
“…In addition, they reported that the heritability of DO was 0.05 for both parities and estimates of heritability for FSCR was 0.01 in first lactation and 0.0 in second lactation. Consistent with our results, Jamrozik et al (2005) reported heritabilities of most reproductive traits were generally below 0.10. Table 3 shows genetic and phenotypic correlations among reproductive performance traits and Table 4 shows genetic and phenotypic correlations among MUN and reproductive performance traits.…”
Section: Resultssupporting
confidence: 91%
“…In cattle, Jamrozik et al (2005) have estimated the proportions of maternal genetic variance of the total variance for fertility traits such as the interval from first service to conception, the non-return rate at 56 days, and stillbirth, using linear models. Even though these are not quite compatible with the foaling (or calving) rate, they offer some comparison to our results.…”
Section: Pedigrees and Inbreedingmentioning
confidence: 99%
“…Threshold models have been used in similar studies on bovine fertility (Kadarmideen et al, 2000;Guerra et al, 2006) and in a twinning study for horses (Wolc et al, 2006), but linear models are used as well (Jamrozik et al, 2005). For a dichotomous variable that is based on an underlying normally distributed trait such as the foaling rate, a threshold model would be theoretically correct.…”
Section: Pedigrees and Inbreedingmentioning
confidence: 99%
“…Focussing on increasing genetic merit primarily for yield reduces genetic merit for fertility (Veerkamp et al, 2003), but conjoint improvement for reproductive performance and milk yield, say maintaining 70% to 80% of the yearly increase in yield (Veerkamp et al, 2000), is possible (Andersen-Ranberg et al, 2005;Jamrozik et al, 2005). In line with this, most leading dairy cattle breeding programmes incorporate fertility, as derived from calving dates and insemination dates, in their selection indices (Miglior et al, 2005).…”
Section: Introductionmentioning
confidence: 99%